La difesa della donna ebrea: Sara Copio Sullam e Debora Ascarelli (Altre Modernità, 2014)
Sara Copio Sullam and Debora Ascarelli, the best-known Jewish women poets of the age of the Italian ghetto, have often been studied with a focus on the distinctive features of their writing: the former as a translator of sacred texts, the latter as the author of original verses, sometimes written as a risposta per le rime (reply through rhymes) or in defence of her orthodoxy. They share, however, a common theme, which has often been neglected: the defence of the Jewish woman, which is overt in some of Copio’s sonnets and prose, whereas it has not yet been properly pointed out in some of Ascarelli’s verses. This paper aims at bringing this theme to the fore not only in Copio, through a rereading of some passages of her Manifesto, but also in Debora Ascarelli, through an analysis of her few original verses. These hendecasyllables certainly reflect the Petrarchan and classicistic atmosphere of the late 16th century in Rome, but they are far from the mainstream modes of women’s poetry of the age. They allow us, therefore, to highlight, besides the differences, the similarities between the two poetesses; their commitment, in the late 16th and early 17th century, to the intellectual and moral defence of the Jewish woman, in a context of general depreciation of women, but also in the background of the claim to the “nobility and excellence of women”.
Keywords: Letteratura ebraica in Italia; Roma; Venezia; Sara Copio Sullam; Debora Ascarelli; Seicento